THE ROLE OF VALUES IN THE DEVELOPMENT OF MORAL EDUCATION IN STUDENTS (Academicia Globe: Inderscience Research, 2023)
This article presents an analysis of the inimitableness of early adolescence and the factors of development of moral awareness during puberty, as well as the methodology for determining moral qualities in students.